RESEÑA de : Pardo Rodríguez, Mª Luisa. La cancillería de don Fernando de la Cerda, infante de Castilla y León (1255-1275). León : Universidad de León-Caja España, 2009. - López Villalba, José Miguel (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2009)
-